Tools and algorithms for decision making - Dmytriienko, Valerii Dmytrovych; Zakovorotniy, O.; Bulba, Serhii Sergiyovich (National Technical University "Kharkiv Polytechnic Institute", 2022)
In the laboratory workshop there are 8 laboratory works on different methods and decision algorithms. At the beginning of each work the theoretical bases are stated research methods or algorithms of decision making in technology or economics. Laboratory work is well illustrated by examples, each laboratory work has individual tasks for students. In the laboratory workshop is considered in detail decision-making criteria in conditions of uncertainty and risk, optimal methods behavior in conflict situations, which are described using game theory, decision making using vector criteria. Designed for full-time and part-time students in the field «Computer Engineering» and «Computer Science».
Keywords: laboratory workshop; risk; research of decision-making criteria in conditions of uncertainty; investigation of criteria with regrets; matrix games; computer science; information technology